Biological effects on Palmer amaranth surviving glufosinate. Issue 4 (9th October 2022) - Jones, Eric; Leon, Ramon. G.; Everman, Wesley Jay
Abstract: Palmer amaranth ( Amaranthus palmeri S. Watson) is a difficult weed to manage due to competitive growth, fecundity, and evolved herbicide resistance. Limited information exist on the fecundity of vegetative stage Palmer amaranth surviving glufosinate applied at different timings. In addition, research has not investigated the germination or glufosinate susceptibility of the offspring from these surviving plants. Field experiments were conducted across three locations in 2019 to determine (a) the fecundity of Palmer amaranth plants surviving glufosinate applied at different vegetative growth stages, and (b) if the offspring from the surviving plants exhibited differential germination and susceptibility to glufosinate. Palmer amaranth was treated at three different vegetative sizes (5 cm, 7–10 cm, > 10 cm) and orthogonal combinations of these application timings. The application timings corresponded to early‐, mid‐ and late‐postemergence applications. Palmer amaranth plants surviving the mid‐, late‐, and the mid postemergence followed by late postemergence glufosinate application were fecund. Palmer amaranth plants surviving the mid postemergence followed by late postemergence application produced less seed than the plants surviving the mid postemergence and late postemergence application. Palmer amaranth was controlled with other glufosinate applications resulting in no seed production. Germination was affected across location and glufosinate treatments, but no clear trend/pattern was observed. The offspring from Palmer amaranth plants surviving glufosinate applications were controlled by all glufosinate rates tested. These experiments provide evidence that Palmer amaranth surviving glufosinate in the vegetative stages may remain fecund, but fecundity can vary with application timing. No measurable effect on the offspring germination or susceptibility to glufosinate was apparent. Core Ideas: Palmer amaranth (∼10 cm) surviving glufosinate will remain fecund (2, 400–22, 000 seeds female −1 ). Seeds from Palmer amaranth surviving glufosinate do not exhibit differential viability or germination. Plants from surviving Palmer amaranth do not exhibit reduced glufosinate susceptibility after one generation.